Antibiotics Versus Appendectomy for Acute Appendicitis - Muhammad Tahir Ali, Muhammad Azhar, Munawer Latif Memon, Muhammad Asif, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the efficacy of antibiotic treatment versus appendectomy in treatment of acute appendicitis. Study Design: Retrospective study Place and Duration of Study: Department of Surgery, Shahida Islam Medical Complex, Lodhran from 1st January 2021 to 31st March 2022. Methodology: One hundred patients of age >18 years were enrolled after the complete assessment and confirmation of acute appendicitis. The clinical confirmation included the complete assessment of signs and symptoms of patients through Modified Charlson Index and Alvardo score. Patients were further divided into two groups with each group having 50 patients and matched for their clinical symptoms and duration. Group A had those patients who were only given antibiotics for the treatment of their acute appendicitis while Group B had those patients which were planned for appendectomy. A course of amoxicillin with clavulanic acid or fluoroquinolone was given for 7 to 10 days and the metronidazole/tinidazole was added in 60% of the cases. Patient’s data was recorded on well structured questionnaire. Results: The mean age was 37.5±11.2 years in group A and 38.1±10.9 years in group B. There were higher numbers of males in both groups. The average incidence of complications like perforation as well as peritonitis and surgical wound infection were significantly less in appendectomy patients and was reported as 17, 12 and 1% respectively. The long-term outcomes of antibiotic treatment plan for acute appendicitis showed requirement of appendectomy in 26% cases in group. Conclusion:Antibiotic treatment can be used effectively for acute appendicitis in selected patients with careful follow up/ monitoring for complications and as an interim treatment option for patient’s not opting for surgery or cannot undergo surgery, however appendectomy remains the most appropriate treatment for acute appendicitis overall. Keywords:Acute appendicitis, Antibiotics, Appendectomy, Efficacy